Analysis of High School Learners' Retellings as a Means of Diagnosing the Quality of Reading and Comprehension of Academic Text - Svetlana V. Shustova; Mariia B. Kazachkova; Khalida N. Galimova; Marine V. Shirinyan (National Research Mordova State University, 2022)
Introduction. This article deals with the problem of studentsʼ understanding of educational texts and ways of diagnosing the level of perception and understanding of secondary texts. The relevance of the study lies in the importance of ways of interpreting and diagnosing the level of perception of educational texts to eliminate the objective reasons for the lack of understanding of educational texts and for further linguistic and psycholinguistic research on this problem. The aim of the article is to describe the results of the experiment aimed at investigating the denotative structure of instructional primary and secondary texts using comparative propositional analysis. Materials and Methods. The experiment involved 200 fifth-grade students of secondary schools in the Republic of Tatarstan. The material used was the social studies text for the 5th grade, edited by L.N. Bogolyubov and L.F. Ivanova, and the secondary texts - retellings performed by students. To study the problem we conducted a preliminary test of the respondents, in order to diagnose the levels of students' perception and understanding of the original text the group of experts carried out a propositional analysis of the retelling. Results. In the course of the research it was revealed that the propositional analysis of texts-retellings and the subsequent comparison of denotative structures of the original and secondary texts are productive and informative procedures for identifying an objective picture of the perception and understanding of texts by schoolchildren. Propositional analysis of the texts showed that most of the experiment participants were able to identify the main idea of the read text and separate the main data from the secondary one. There is a discrepancy in the number of retained propositions in the retellings; the volume of the text varies significantly: semantic additions, simplifications, collapses, and offsets are detected. There is a partial restructuring of the propositions of the original text. The fact of discrepancy in the number of retained propositions is explained by the level of understanding of the primary text, interpretation of the text content and it may be due to the peculiarities of adolescent thinking. Background knowledge of the recipients, their emotional attitude, practical skills of independent work with the text, the ability to extract basic information from the text also affect the success of the retellings. Discussion and Conclusion. Materials of the article can be useful for elimination of objective reasons for misunderstanding of educational texts and for further pedagogical and psycholinguistic research.